The role of basal slip in the generation of intergranular stresses in magnesium alloy studied using X-ray diffraction and modelling. (April 2021) - Baczmański, A.; Wroński, M.; Kot, P.; Wroński, S.; Łabaza, A.; Wierzbanowski, K.; Ludwik, A.; Marciszko-Wiąckowska, M.
Abstract: Characterisation of the residual stresses at a scale of polycrystalline grains is the main topic of this work. The grazing incidence X-ray diffraction during "in situ" tensile test and a novel method of experimental data interpretation allowed to determine the evolution of macroscopic and intergranular stresses (the second order stresses) during elastic-plastic deformation and elastic unloading of AZ31 alloy sample. Additionally, the values of the critical resolved shear stresses were determined for slip systems activated during plastic deformation. A new important finding of this work is the determination of significant residual intergranular stresses in textured magnesium alloy subjected to plastic deformation. These stresses are correlated with the orientation of basal plane with respect to the applied stress, and they can be explained by a large difference between critical resolved shear stress values for basal and non-basal slip systems. In contrast to the magnesium alloy studied in this work, low values of the second order stresses were found previously in a two-phase Ti alloy due to the small difference between critical resolved stresses in both phases. Graphical abstract: Unlabelled Image Highlights: X-ray diffraction can be used to determine CRSS values and integranular stresses. The most grains in textured AZ31 alloy exhibit small values of second order stresses. Large incompatibility stresses are generated during tensile test due to low CRSS for basal slip. Partial relaxation of the second order stresses occurs during sample unloading.